ISO 14001 and beyond : environmental management systems in the real world - Sheldon, Christopher (Sheffield, England : Greenleaf, 1997)
On September 1st 1996, ISO 14001 was published, worldwide. Written over five years in consultation with international industrial experts, non-governmental organisations and regulators, this environmental management systems standard will help organisations manage their impacts on the environment, no matter what their size, nature or location. The implications for the future are enormous. But what does the standard mean in the real world? What changes do managers have to make to accommodate its principles? What decisions need to be faced and when? Is it really going to make a difference or is it just another case of global greenwash? Will it be another missed opportunity for you, your organisation, or your market?At the start of what promises to be a worldwide explosion of interest in standardised EMSs, ISO 14001 and Beyond looks at their creation, their use, and their limitations, attempting to discover the essential truth about this important management tool.
Beyond 14001 / Dick Hortensius and Mark Barthel -- Neither international nor standard / Harris Gleckman and Riva Krut -- ISO 14001 environmental management systems standard / Christopher L. Bell -- Squaring the circle / Mark Smith -- Trade, competitiveness and the environment / Donal O'Laoire -- Environmental management standards and certification / Tim J. Sunderland -- Environmental management systems / Jim Hutchison, Anatoly Pichugin and Ann Smith -- Attitudes and experiences of the Japanese business community vis-à-vis EMS standards / Tomoko Kurasaka -- Environmental management systems / Aidan Davy -- Training and environmental management systems / Andy Wells -- Environmental management standards / Andrew Blaza and Nicky Chambers -- Targeting sustainability / Philip Sutton -- From EMAS to SMAS / Andrea Spencer-Cooke -- Beyond ISO 14001 / Philip M. Stoesser -- EMAS implementation at Hipp in Germany / Matthias Gelber, Bernhard Hanf and Sven Hüther -- Training / Gabriele Crognale -- Eco-management and audit scheme for UK local authorities / Nigel Riglar -- Environmental management standards / Ruth Hillary -- Towards innovative, more eco-efficient product design strategies / J.M. Cramer -- Establishing workable environmental objectives / Alison Bird -- Environment risk / David Shillito.
Includes bibliographical references and index.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: ISO 14000 Series Standards; Environmental protection -- Standards; Manufactures -- Environmental aspects; Environmental policy -- Standards; Environmental auditing -- Standards; Electronic books